Formação continuada de professores de educação física na perspectiva da inclusão - Nascimento, Sylvia Fernanda (2012)
We try to answer which the implications of an action of continued formation to/in pedagogical practice of the professors of physical education in the inclusion process. To form the professors participants group was organized a extension project entitled for “Continued Formation of Professors of Physical Education for the Inclusive Education”, with the objective to originate the Operative Group of Formation (GOF). The action of formation continued has only a class, in the period of february until june in 2011, in a weekly reunion, with 20 meetings, and totalfinal hours of 120. The formation meeting had counted at the beginning with seven professors on the activities and it firmed with four professors until the end of the process. We adopt as main methodological way, the use of some elements of theory of the research-action pointing with respect to perspective of the critical research-action. We use as instruments and procedures of collection of data the resources technician: narrative, daily of field and interview. We analyze four categories - the formation of the professors in quarrel; practical pedagogical inclusive: reflecting the teaching paper in the physical education; practical politic-pedagogical and the confirmation of the physical education; perception of the professors on the process of formation tried in the GOF - that they had guided the quarrel in the present study. To the end of the process we evidence that this action of formation, when articulated with the professors, it estimates better answers to the real necessities of them. We undertake an action of continued formation of professors of physical education where the referring demands and necessities to the inclusive education had been heard and argued, having for base the reflexive practical, in which the participants, collectively and collaboravely, could produce a different one to look at, a direction differentiated on its reality, generating incremental changes, valuing its to know/to make.